A comprehensive review of stage-of-the-art subsystems configurations, technical methodologies, advancements, and prospects for new energy electric vehicles - Zhang, Chi; Jasni, Jasronita; Mohd Radzi, Mohd Amran; Azis, Norhafiz; He, Xiangming (Springer, 2023)
The signifcant challenges are fossil fuel dependence, climate change, and incremental energy cost in the twenty-frst century. Looming environmental problems and growing concerns about the global energy crisis, individuals and organizations have sought new opportunities and technologies to meet the growing demand for clean and sustainable energy systems. Electrifcation of transportation system is a promising way to green transportation system and reduce climate change. In recent years, new energy electric vehicles (NEEVs) have become increasingly popular in the automotive industry and are poised to replace the internal-combustion engine (ICE) to protect environment from pollution. This paper provides an indepth investigation into the present status, latest deployment, and future prospects in the implementation of NEEVs while introducing the subsystems and their components: electrifcation transportation degrees, power battery pack, electrical propulsion system, charring architecture, and international standards. Additionally, extending from limited knowledge and ability, the enabling technologies and prospects for future development of NEEVs are also presented in this paper. A total of 131 publications are arranged and appended for quick referencing. It is envisaged that researchers and engineers involved in these felds could fnd this paper very valuable and a one-stop source of rich information.